Pengujian Karakteristik Sensoris Teh Herbal Perikarp Manggis (Garcinia mangostana), Kayu Manis (Cinnamon verum), dan Cengkeh (Syzygium aromaticum): Pengaruh Formulasi Teh Herbal Perikarp Manggis (Garcinia mangostana), Kayu Manis (Cinnamon verum), dan Cengkeh (Syzygium aromaticum) terhadap Tingkat Penerimaan Konsumen - Pratiwi, Yunita Satya; Sanjaya, Yushinta Aristina; Rahmawati, Rahmawati; Putri, Larestananda Asmaul Husna Hizaumi; Syari, Ririef Mutiara (Universitas Airlangga, 2024)
Background: Herbal tea Is one of the herbal drinks that has been widely consumed by Indonesian people and known as tea that have functional properties, one of them is source of antioxidants. Antioxidants can be obtained from a lot of sources, such as the mixture of mangosteen pericarp, cinnamon, and cloves. The use of cinnamon and clove expected to increase the consumers' preference towards this tea. Objectives: This research aims at evaluating the acceptance level of several sensory parameters of tea made of mixture of mangosteen pericarp, cinnamon, and clove. Methods: The experimental design used in this research was completely randomized design with three replications, resulting in 27 samples of herbal tea. Besides, the data obtained from panelists will be analyzed by using Analysis of Varian (ANOVA) and followed by Duncan's Multiple Range Test (DMRT) in SPSS 25.0 software. Results: The results show that the addition of cinnamon and cloves showed a significant difference. The more addition of spices will lower the panelist score. It can be seen in the sample containing 24 grams of mangosteen pericarp, 3 grams of cinnamon (B4) which had the highest panelist score in color, taste, and bitterness aspects. While the lowest panelist score was obtained by a sample containing 12 grams of mangosteen pericarp, 3 grams of cinnamon and cloves (A1). Conclusions: The more spices added, especially cloves will reduce the liking score. The result obtained by this research can be used for optimization of the best formula so maximum points can be known.